2017
DOI: 10.5301/hipint.5000526
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Impingement Syndromes around the Hip Joint

Abstract: Impingement syndromes are increasingly recognised as significant causes of hip pain and dysfunction. A broad spectrum of intraarticular and extraarticular conditions has been implicated in their pathophysiology. Physical examination is often inconclusive as clinical findings may be unclear or misleading, often simulating other disorders. With current improvements in imaging techniques and better understanding of hip impingement related pathomechanisms, these entities can be accurately diagnosed. In addition, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 112 publications
0
7
0
Order By: Relevance
“…Although narrowing of the IF and QF spaces accompanied with QF edema is sensitive radiographic markers for the IFI syndrome [ 10 ], its exact pathophysiology remains disputed [ 14 ]. Papavasiliou et al [ 15 ] reported reduced IF and QF spaces in non-symptomatic young athletes and Stenhouse et al [ 7 ] found bilateral QF edema in young patients with unilateral symptomatology, as we did in our case ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although narrowing of the IF and QF spaces accompanied with QF edema is sensitive radiographic markers for the IFI syndrome [ 10 ], its exact pathophysiology remains disputed [ 14 ]. Papavasiliou et al [ 15 ] reported reduced IF and QF spaces in non-symptomatic young athletes and Stenhouse et al [ 7 ] found bilateral QF edema in young patients with unilateral symptomatology, as we did in our case ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Images of 3-dimensional computed tomography (3D-CT) are widely used for cam evaluation because they provide better evaluation of bony structures than magnetic resonance imaging (MRI). 16,28 Yet, it is still largely left to the surgeon’s experience to define the cam borders on 3D-CT. 31,32…”
mentioning
confidence: 99%
“…It has been reported that the alpha angle can be measured effectively on MRI oblique axial, oblique coronal, and radial views, 13 but it can not be accurately evaluated on the standard axial and coronal CT views because the scanning directions are not parallel to the long axis of the femoral neck. 23,24 Recently, CT multiplanar reconstruction has been introduced for cam evaluation, 28 in which the CT images are reformatted based on the same scanning direction as hip MRI. Therefore, the markers of the cam border can be defined on the reformatted 2D-CT images using the AAM method, and then 3D-CT can display the area of cam deformity after the markers are imported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Although FAI was originally described as cam or pincer bony impingement, it is usually accompanied by soft tissue lesions (labrum, ligamentum teres hip musclestendons, hip capsule) and cartilage defects. 3,4 Femoroacetabular impingement syndrome is a multifactorial disease due to genetic predisposition, the presence of hip dysplastic changes, history of a pediatric hip disease, and excessive or abnormal joint overloading during hip mobilization. 3,5 Various sports have been reported to increase the risk of FAI development, especially when hip flexion or extension is combined with rotational movements or repetitive extreme hip range of motion is obtained during performance.…”
mentioning
confidence: 99%